Specific and multiple‐target gene silencing reveals function diversity of BnaA2.NIP5;1 and BnaA3.NIP5;1 in Brassica napus. (13th May 2021) - He, Mingliang; Zhang, Cheng; Chu, Liuyang; Wang, Sheliang; Shi, Lei; Xu, Fangsen
Abstract: Rapeseed ( Brassica napus ) is an economically important oilseed crop in the world, but its production is strongly dependent on boron (B) supplies. Major intrinsic protein NIP5;1 is essential for B uptake and plant development under B limitation. In this study, phylogenetic and expression analyses identified two NIP5;1 orthologue genes, BnaA2.NIP5;1 and BnaA3.NIP5;1, which are mainly expressed in roots of B. napus . Specific and multiple‐target RNAi was used to suppress BnaA3.NIP5;1 or both BnaA2.NIP5;1 and BnaA3.NIP5;1 expression in B‐efficient rapeseed Qingyou 10 (QY10), respectively, for revealing the roles of BnaA2.NIP5;1 and BnaA3.NIP5;1 in low‐B tolerance in B. napus . We found that both BnaA2.NIP5;1 and BnaA3.NIP5;1 are important for B. napus normal growth under low‐B conditions, while these two genes have distinct roles. BnaA2.NIP5;1 is mainly expressed in the epidermis cells, which is required for efficient B uptake into roots, hence for B translocation to the shoots. BnaA3.NIP5;1 is specifically localized in the distal part of lateral root cap cells to promoter root elongation under low‐B conditions, which is important for seed production in the maturity stage of B. napus . Taken together, our specific and multiple‐target RNAi strategy provides novel insights into the gene function diversification between BnaA2.NIP5;1 and BnaA3.NIP5;1, such an approach can be potentially applicable to other polyploid crops. Abstract : Specific and multiple‐target RNAi strategies provide novel insights into the gene functional diversification between BnaA2.NIP5;1 and BnaA3.NIP5;1 in rapeseed ( Brassica napus ). BnaA2.NIP5;1 is mainly expressed in the epidermis cells, which is required for efficient B uptake into roots, hence for B translocation to the shoot. BnaA3.NIP5;1 is specifically localized in the distal membrane of LRC cells to promoter root elongation under low‐B conditions, which is an important seed production in the maturity stage of B. napus .